Pembatalan pada Peralihan Hak Milik Atas Dasar Hibah - Luna Alifia Khansa; Surahmad Surahmad (Wajah Hukum, 2021)
The grant would be an outright gift from the giver to the gritty and while the giver was still alive. The grant can be poured in 2 deeds which are authentic deeds and under hands which have a different legal certainty. The legality of handheld grants and the reason for the cancellation of many are not specified in the regulations. Although the cancellation of the grant has been emphasized for not being able to return with an exception in article 1688 code civil, there still remains in practice a case requesting the cancellation of the grant for various things. The purpose of this research is to provide information regarding the legality of the grants under the hands and anything that might invalidate the grant. The study method used in this study was normative-juridical with a constitutional approach. The results of this study are under his hands still valid, but at the time of registration according to page no.24 of 1997 still have to use a deed made by ppat. Then the reason for the cancellation of the grant itself is not only admissible in article 1688 code civil, but there is another reason for the cancellation of grants such as administrative law cacies, grants exceeding the limit of legitme portie, and so on.